(untitled) (Research, Society and Development, 2022)
COVID-19 is a new coronavirus respiratory disease caused by SARS-CoV-2, first described in China in December 2019 and since March 2020 has been affecting the whole world. The principal mode of transmission is through exposure to respiratory droplets carrying infectious virus. Contact with contaminated surfaces or objects (fomites) is also possible, although the risk is generally considered low. However, the widespread community viral transmission makes it difficult to experimentally demonstrate human contagion via fomites. As human coronaviruses can be found on inanimate surfaces for hours up to days (depending on the inoculum shed), in materials as metal, glass or plastic, waste management can pose a problem in the context of the spread of the disease. Thus, the main objective of this work was to discuss the influence of poor waste management for the spread of SARS-CoV-2 in the state of Minas Gerais, Brazil, based on the first reported cases in 853 cities. Therefore, different variables related to socioeconomic data, waste management services, and number of COVID-19 confirmed cases were correlated and discussed. Overall, the associations found in this study in relation to reported cases and poor waste management raise the need for attention to this issue, which is still little explored despite being potentially aggravating for numerous diseases.